Cybersecurity education for the elderly as a strategic tool to mitigate digital economic risks - Brata, Daffa Mahdy; Putra, Bainul Dwi Tri; Anindito, Anindito (Economic Military and Geographically Business Review, 2026)
Background: The vulnerability of older people to online fraud has increased drastically, with national losses reaching IDR 2 trillion by April 2025. These frauds pose a significant threat not only to the elderly but also to the stability of Indonesia’s financial sector and fintech industries, highlighting the need for systemic solutions that protect both individuals and businesses. This study aims to develop a cybersecurity education application for the elderly, which not only addresses common fraud patterns in Indonesia, such as fake lotteries, digital bank fraud, and WhatsApp social engineering, but also serves as part of a broader strategy to protect the digital economy, mitigate business risks, and strengthen financial sector security. Methods: The study uses the R&D method with the analysis, design, development, implementation, evaluation model. The application features an elderly-friendly interface with large fonts, simple navigation, and adaptive learning. User testing was conducted with elderly participants to assess usability and effectiveness, incorporating experiential learning principles to enhance engagement. Findings: Initial prototype evaluation with 15 elderly participants (aged 62-74) showed that 87% successfully completed basic navigation tasks independently, and 73% completed the full learning flow without assistance. The experiential learning approach integrated into the prototype design proved more effective than traditional lecture-based methods in preliminary testing. Common usability challenges identified included back navigation difficulties (40% of participants) and quiz submission confusion, informing iterative design improvements. Conclusion: This application offers a sustainable, cost-effective solution that not only reduces cybercrime-related losses among the elderly but also contributes to a broader strategy of economic digital security. Novelty/Originality of this article: This research introduces a unique approach that combines cybersecurity education for the elderly with strategies to mitigate economic risks in the digital economy. The application integrates an elderly-friendly interface and experiential learning techniques to enhance digital literacy, while simultaneously offering a scalable solution to reduce the broader impact of online fraud on the financial sector.